2020
DOI: 10.1002/adfm.201909087
|View full text |Cite
|
Sign up to set email alerts
|

Active Reconfigurable Tristable Square‐Twist Origami

Abstract: Origami structures offer valuable applications in many fields, ranging from metamaterials to robotics. The multistable characteristics of origami structures have been pursued for acquiring unique reconfigurable features. For achieving this goal, an unusual polymeric tristable origami structure is demonstrated using a classic square‐twist origami configuration. By manipulating both material properties and geometric parameters of the heteropolymer structures, a design principle for tailoring the multistable conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 42 publications
0
93
0
Order By: Relevance
“…[ 22 ] Equations 2 and 3 are solved simultaneously with the mass transport (Equation S19, Supporting Information), charge equilibrium (Equation S20, Supporting Information), and the stress equilibrium equation. Stress evolution at the interface involves complicated contact mechanics, [ 26,32 ] creep or viscoplastic behavior of Li metal, [ 25,33 ] and the volumetric change of the electrode. To make the problem mathematically tractable, we assume that the inelastic strain due to the volume expansion of Li metal is the only source of the internal stress generation, and the contact mechanics is not considered.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] Equations 2 and 3 are solved simultaneously with the mass transport (Equation S19, Supporting Information), charge equilibrium (Equation S20, Supporting Information), and the stress equilibrium equation. Stress evolution at the interface involves complicated contact mechanics, [ 26,32 ] creep or viscoplastic behavior of Li metal, [ 25,33 ] and the volumetric change of the electrode. To make the problem mathematically tractable, we assume that the inelastic strain due to the volume expansion of Li metal is the only source of the internal stress generation, and the contact mechanics is not considered.…”
Section: Resultsmentioning
confidence: 99%
“…The solid interfaces with favorable bifunctional conductivity for electron and ion are essential in principle, [ 7 ] but the complex interfaces involve in physics, chemistry, and mechanics, lying at the heart of the solid‐state battery concepts. [ 8 ] Therefore, deep understanding of the interface behavior and mechanism of the all‐solid‐state lithium batteries is a necessity. Interface issues in the solid‐state batteries can be understood from two aspects, interface physics and interface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a number of studies have shown that electro‐chemo‐mechanical coupling strongly affects the interfacial stability of solid‐state batteries (SSBs). [ 35,36 ] One the one hand, local strain influences the interfacial contact and the electrochemical reaction rates. On the other hand, the electrochemical deposition of lithium can further cause mechanical deformation at the interfaces, forming a feedback loop.…”
Section: Introductionmentioning
confidence: 99%